Effect of filtration mode and backwash water on hydraulically irreversible fouling of ultrafiltration membrane. (July 2017) - Chang, Haiqing; Liu, Baicang; Liang, Heng; Yu, Huarong; Shao, Senlin; Li, Guibai
Abstract: To investigate the effect of filtration mode and backwash water on ultrafiltration (UF) membrane performance, total fouling index (TFI) and hydraulic irreversible fouling index (HIFI) for constant pressure (CP) filtration and constant flux (CF) filtration were compared. Kaolin, humic acid (HA) and sodium alginate (SA) solutions were used as feed solutions, and then the fouled membranes were backwashed with UF permeate or ultrapure water. Results showed that when the kaolin solution was filtrated, the filtration mode had a limited effect on the membrane fouling, and low TFI and HIFI were observed. When HA and SA solutions were filtrated, the TFI of UF under CP mode was comparable to or slightly higher than that under CF mode. Higher TFI was observed at a hydrophobic membrane, a high filtration strength, a high feed concentration, a low pH, a high ionic strength, and a low Ca 2+ concentration. When the UF permeate was used as the backwash water, the HIFI for the UF operated under CF mode was significantly less than that under CP mode. Low irreversible fouling was obtained when the ultrapure water was used for backwashing, and the HIFI for the UF under different filtration modes was almost identical. Graphical abstract: Highlights: UF membrane fouling under constant pressure (CP) and constant flux (CF) was compared. Comparable TFI was obtained under CP and CF modes for all the feed solutions tested. HIFI for kaolin solutions was hardly affected by filtration mode and backwash water. HIFI for organics largely depended on backwash water quality and filtration mode. CF filtration excelled CP one when UF permeate backwashed organic-fouled UF membrane.